Nociceptive sensory neurons promote CD8 T cell responses to HSV-1 infection - Jessica Filtjens (Nature Portfolio, 2021)
Herpes simplex virus 1 (HSV-1) is a neurotropic virus that often cause pain via the induction of ulcer or blisters. Here the authors show, in mouse models of HSV-1 infection, that the pain-perceiving nociceptor Nav1.8 + neurons contribute to regulating both innate and adaptive immune responses against HSV-1, thereby offering a potential target for therapy.